“How PrEPared are you?”: Knowledge of and attitudes toward PrEP among overseas-born and newly arrived gay, bisexual, and other men who have sex with men in Australia - Sudarto, Budiadi; Chow, Eric P. F.; Medland, Nicholas; Fairley, Christopher K.; Wright, Edwina J.; Armishaw, Jude; Price, Brian; Phillips, Tiffany R.; Ong, Jason J. (Frontiers in Public Health, 2022)
Introduction Overseas-born and newly arrived gay and bisexual men and men who have sex with men (GBMSM) are at higher risk of acquiring HIV in comparison to Australian-born GBMSM. Pre-exposure prophylaxis (PrEP) is subsidized by the Australian government under Medicare, Australia's universal health insurance scheme, however many members of this population are Medicare-ineligible, which could prevent them from accessing PrEP. We wanted to explore participants' knowledge of and attitudes toward PrEP and their opinions of new PrEP modalities, namely injectable PrEP and PrEP implants. Methods We conducted in-depth qualitative interviews between February 2021 to September 2021 with 22 overseas-born, newly arrived (<5 years in Australia) GBMSM of varying PrEP use. We asked their opinions of PrEP and their preferences of new PrEP modalities. Interviews were audio recorded and transcribed verbatim. We conducted a reflexive thematic analysis to interpret the data. Results Participants' views reflect the intersections between systemic factors, such as Medicare ineligibility and the high cost of PrEP, with socio-cultural factors, such as lack of knowledge about PrEP, internalized stigma stemming from homo- and sex-negativity, and stigmatizing attitudes toward PrEP and PrEP users. For participants who were on PrEP, being community connected, having a positive relationship with doctors and nurses, and being informed of the option to purchase PrEP from overseas pharmacies at a low cost helped them to overcome some of these barriers. Additionally, there was a strong preference for injectable PrEP but not PrEP implants. Participants stressed the importance of providing a comprehensive information about PrEP specific to this population and to make PrEP free for all. Conclusions We concluded that resources about PrEP specific to this population that address both systemic and socio-cultural factors are needed, and for these resources to be available in languages other than English. This is to coincide with on-going advocacy to increase the capacity of publicly funded sexual health clinics to provide multilingual PrEP services for people without Medicare, and to make PrEP free for all. These combined strategies have the potential to increase PrEP knowledge and uptake among this population.